Do You Face a Dark Triad Leader at Your Organization? A Descriptive Study on the Educational Sectors in the UAE - Parameswaran, Hima; Elsawy, Mahmoud (Archives of Business Research, 2022)
In this twenty-first century, leadership qualities are paramount for fostering organizational culture and employee performance. This study penetrated the negative aspects of leadership qualities ‘dark-triad of leadership’ and its impact on team members. The hypotheses were developed from a thorough literature review on dark triad traits namely Narcissist, Machiavellian, and Psychopath. To reveal the impact of traits amongst team members, the Emirati educational sector was selected, and questionnaires were distributed amongst different strata by the random sampling technique. The responses were analyzed using SPSSv27. The analysis validated the reliability of the data and confirmed the hypotheses. Furthermore, it illuminates the intricate and challenging field of leadership research. Indeed, the study can develop organizational culture and employee performance.